PENERAPAN METODE AHP DAN SMART DALAM PEMILIHAN PROVIDER WIFI DI KOTA PALEMBANG - Michael Darwin; M. Rudi Sanjaya; Dedy Kurniawan; Rizka Dhini Kurnia (LPPM Universitas Abdurrab, 2026)
The demand for fast and stable internet services continues to grow in line with the advancement of digital technology in Palembang City. The wide range of Wi-Fi service providers (Internet Service Providers) with varying characteristics makes it difficult for users to objectively determine the best option. This study aims to apply the Analytic Hierarchy Process (AHP) and Simple Multi Attribute Rating Technique (SMART) methods to support decision-making in selecting the best Wi-Fi provider in Palembang City. The AHP method is used to determine the priority weights of each criterion, including price, internet speed, connection stability, and after-sales service. Meanwhile, the SMART method is used to calculate the preference value of each provider alternative based on the obtained weights. The results indicate that internet speed is the most influential criterion in users’ decision-making, followed by stability, price, and after-sales service. Based on the calculation results, Biznet Home ranked highest with a score of 0.966 (on a maximum scale of 1.0) and is therefore recommended as the best Wi-Fi provider in Palembang City. The integration of AHP and SMART methods proves effective in producing systematic, objective, and easily interpretable decision outcomes for users.